2004
DOI: 10.1002/j.2161-0045.2004.tb00657.x
|View full text |Cite
|
Sign up to set email alerts
|

A Preliminary Investigation of Factors Associated With Job Loss Grief

Abstract: This study investigated relationships among factors hypothesized as related to job loss grief. A summary grief score correlated positively with time since job loss and number of dependents, and negatively with length of notice. Perceived reemployment prospects and income loss related positively to some grief index subscales, as did the condition of living on one's own. Job duration correlated negatively with some grief responses. Implications for counseling and avenues for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0
3

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 14 publications
4
28
0
3
Order By: Relevance
“…Koch, Egbert, Coeling, and Ayers's (2005) qualitative study about people's experience of returning to work after illness found comparable results about people's experience of losing a job, as have other researchers (e.g., Brewington et al, 2004;Wald & Alvaro, 2004). Other researchers also have indicated that social relationships are important for mental and physical health, and connected to the risk of mortality (Umberson & Montez, 2010).…”
Section: The Importance Of Social Relationshipssupporting
confidence: 56%
See 1 more Smart Citation
“…Koch, Egbert, Coeling, and Ayers's (2005) qualitative study about people's experience of returning to work after illness found comparable results about people's experience of losing a job, as have other researchers (e.g., Brewington et al, 2004;Wald & Alvaro, 2004). Other researchers also have indicated that social relationships are important for mental and physical health, and connected to the risk of mortality (Umberson & Montez, 2010).…”
Section: The Importance Of Social Relationshipssupporting
confidence: 56%
“…One of our participants described what we have chosen to call the cobweb of undesired social isolation. He described how ''dangerous it was to lose connections to the world'' and just stay at home, asserting that it was dangerous because it was ''so difficult to break it up,'' as Wald and Alvaro (2004) and Brewington et al (2004) also described. We suggest that the undesired social isolation aspects of reduced working capacity should be studied further.…”
Section: The Importance Of Social Relationshipsmentioning
confidence: 90%
“…The experience can include the loss of identity, social status, self‐respect, financial security, and their assumptive worldview as well as increased health and psychological issues (Walsch, 2009). As Brewington, Nassar‐McMillan, Flowers, and Furr (2004) stated, “It is essential for career counselors to identify clients who are grieving and to be prepared to work with a wide range of grief responses” (p. 81). A career counseling class could incorporate issues of grief surrounding job loss into the curriculum such that career counseling students would be able to intervene with their unemployed clients in the most effective manner.…”
Section: Recommendations For Incorporating Grief and Loss Educationmentioning
confidence: 99%
“…Research suggests job loss leads to feelings not dissimilar to bereavement (Brewington et al 2004). It can contribute to compromised mental (Fryer and Fagan 2003) and physical health (Gallo et al 2000) and loss of self-esteem, community, and identity (Jahoda 1982).…”
Section: Career Change and Transitionmentioning
confidence: 99%
“…Informed by occupational transition theory (Rudisill et al 2010;Brewington et al 2004;Gallo et al 2000;Jahoda 1982), questions about transition experiences were aimed at understanding the participant's psychological and emotional responses during these periods. Hakim's preference theory (2006), which defines 'greedy occupations ' (2006, 279) questions that probed for specific career development challenges.…”
Section: Interview Question Developmentmentioning
confidence: 99%